Flavonol Biosynthesis By Nonheme Iron Dioxygenases: A Computational Study Into The Structure And Mechanism - Neelam Zeb; Muhammad H. Rashid,; Sidra Ghafoor,; Sam P. de Visser; M. Qadri E. Mubarak (Elsevier, 2024)
Journal of Inorganic Biochemistry Volume 198, September 2019, 110728